Increased mortality with intensive control in patients with higher baseline SBP and lower Framingham risk. Issue 5 (7th February 2022) - Pan, Heng-Yu; Lin, Hung-Ju; Chen, Wen-Jone; Wang, Tzung-Dau
Abstract : Objective: In the Systolic Blood Pressure Intervention Trial (SPRINT), the relative reduction in primary outcome with intensive blood pressure (BP) control was numerically smallest in the highest baseline SBP tertile. In this post hoc analysis of SPRINT, the goal was to explore whether the effects of intensive BP treatment varied among patients with different baseline SBP and cardiovascular risks. Methods: Patient-level data from 9361 randomized participants in SPRINT were used. Heterogeneity between treatment and patient characteristics were examined stratified by different baseline SBP levels. Cumulative incidences of primary outcome and all-cause death were compared between treatment groups for patients with baseline SBP at least 160 mmHg and lower Framingham risk. Results: For participants with a baseline SBP of at least 160 mmHg, intensive treatment was associated with a higher rate of all-cause death as compared with standard treatment (1.86 vs. 1.62% per year). After adjustment for age and sex, intensive treatment was associated with significantly increased all-cause death compared with standard treatment [hazard ratio (95% CI) for intensive group: 3.12 (1.00–9.69); P  = 0.049] in participants with an SBP of at least 160 mmHg and a Framingham risk score of 31.3% or less (average of median and geometric mean). Patient outcomes were otherwise similar regarding age, use of antihypertensive therapy, cardiovascular disease or chronic kidney disease. Conclusion: Among the SPRINT participants with a baseline SBP of at least 160 mmHg and a lower Framingham risk score, targeting an SBP of less than 120mmHg compared with less than 140mmHg resulted in a significantly higher rate of all-cause death.